Arab criminology - Ouassini, Nabil (Criminology in focus, 2023)
"The objective of Arab Criminology is to establish a criminological sub-field called 'Arab Criminology.' Presenting compelling arguments and examples that support the establishment of this sub-field, Arab Criminology will be of great interest to Criminology, Criminal Justice, Legal Studies, and Middle Eastern/North African studies scholars, particularly those working on Southern Criminology, Comparative Criminology, International Criminal Justice Systems, and Arab studies"--